Autoperforation of 2D materials for generating two-terminal memristive Janus particles. Issue 11 (November 2018) - Liu, Pingwei; Liu, Albert; Kozawa, Daichi; Dong, Juyao; Yang, Jing; Koman, Volodymyr; Saccone, Max; Wang, Song; Son, Youngwoo; Wong, Min; Strano, Michael
Abstract Graphene and other two-dimensional materials possess desirable mechanical, electrical and chemical properties for incorporation into or onto colloidal particles, potentially granting them unique electronic functions. However, this application has not yet been realized, because conventional top-down lithography scales poorly for producing colloidal solutions. Here, we develop an 'autoperforation' technique that provides a means of spontaneous assembly for surfaces composed of two-dimensional molecular scaffolds. Chemical vapour deposited two-dimensional sheets can autoperforate into circular envelopes when sandwiching a microprinted polymer composite disk of nanoparticle ink, allowing liftoff into solution and simultaneous assembly. The resulting colloidal microparticles have two independently addressable, external Janus faces that we show can function as an intraparticle array of vertically aligned, two-terminal electronic devices. Such particles demonstrate remarkable chemical and mechanical stability and form the basis of particulate electronic devices capable of collecting and storing information about their surroundings, extending nanoelectronics into previously inaccessible environments. A technique of autoperforation is presented to fabricate colloidal microparticles with functional polymer composite enveloped by two sheets of 2D materials. The particles can work as electronic devices with good stability in harsh environment.